Analisis Kandungan Logam Berat Tembaga (Cu) Pada Air Kolam Uji PPNS Dengan Metode Spektrofotometri - Andin Asmara Putri; Putri Anjarwati; M. Arya Maliki Syah Putra; Denny Oktavina Radianto (KOLONI, 2023)
The PPNS (Surabaya State Shipbuilding Polytechnic) Test Pool is a pool used to test the feasibility of various kinds of works that have been made by PPNS students. Due to the increase in human activities that occur, it can cause various kinds of problems, one of which is water pollution. Heavy metals are declared as very dangerous pollutants because of their non-degradable nature (Damaianto & Masduqi, 2014). Heavy metals in the waters are actually also needed by aquatic biota in the metabolic process but in small doses, one of which is heavy metal copper (Cu) which will pollute if the levels are excessive in the waters. Therefore, this research was conducted to analyse the content of heavy metal copper (Cu) as a benchmark and parameter and compare the concentration of Cu with the maximum level in the Government Regulation of the Republic of Indonesia Number 22 of 2021. Analysis of copper (Cu) heavy metal content was carried out by uv-vis spectrophotometric method using 25% ammonia additives and 1% Na - diethyldithiocarbomate. The standard solution and samples that have received the treatment are continued with absorbance and concentration measurements using a spectrophotometer. Based on the results of the study, the average level of heavy metal copper (Cu) contained in the PPNS Test Pool sample water is 1.70 mg/l. Where Cu heavy metal pollution is very high and does not meet the quality standards in Government Regulation of the Republic of Indonesia Number 22 of 2021 with the maximum level of copper heavy metal (Cu) is 0.02 mg/l. Keywords: Heavy metal coper (Cu), spectrophotometry, water pollution, PPNS test pool